Collectivism and employment relations in Denmark: underpinning economic and social success. (3rd July 2021) - Rasmussen, Erling; Høgedahl, Laust
ABSTRACT: In recent decades, there have been many positive evaluations of Denmark. This article will focus on the role that employment relations and in particular collective bargaining has played in the economic and social success of Denmark. The so-called Danish Model of employment relations with its emphasis on voluntary collective bargaining and supported by 'flexicurity' (flexibility for employers and security for employees) has influenced international debates on economic, social and employment relations policies. Although 'flexicurity', comprehensive collective bargaining arrangements and high union density are often mentioned in research on the Danish Model, this article will argue that two other important factors have played a crucial role in underpinning the longevity and success of the Danish Model. First, employer collaboration with unions and their supporting collective bargaining at both central and local level is vital. Danish employer organisations have been active in adjusting the collective bargaining system but they have also been supportive of voluntary collective bargaining as a cornerstone of the Danish Model. Second, strong employer support is further underpinned by institutionalised workplace collaboration and the article argues that this aligns national and industry collective bargaining with employee involvement in workplace working arrangements and changes.